2013
DOI: 10.1080/07399332.2012.736571
|View full text |Cite
|
Sign up to set email alerts
|

Educating Women for HIV Prevention: Does Exposure to Mass Media Make Them More Knowledgeable?

Abstract: Mass media is an important vehicle for health promotion in developing countries. In Bangladesh multiple media campaigns are being carried out to educate people about HIV/AIDS. We examined the extent of HIV/AIDS knowledge and the association of exposure to mass media among women in Bangladesh. The Bangladesh Demographic and Health Survey (BDHS) provides data for this article. We found that media exposure (combined index of television, radio, and newspaper) was a highly significant predictor of women's knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 59 publications
5
30
0
Order By: Relevance
“…women who did not use contraception did not have enough sexual autonomy to refuse sex with an STDinfected husband/partner, as they may not be empowered to make this decision. These findings bear resemblance to the results of other studies [9,[15][16][17][18][19].…”
Section: Behavior Regarding Stds and Hiv/aidssupporting
confidence: 91%
See 2 more Smart Citations
“…women who did not use contraception did not have enough sexual autonomy to refuse sex with an STDinfected husband/partner, as they may not be empowered to make this decision. These findings bear resemblance to the results of other studies [9,[15][16][17][18][19].…”
Section: Behavior Regarding Stds and Hiv/aidssupporting
confidence: 91%
“…Several similar studies also indicated that knowledge and awareness of STDs and HIV/aIDS reduce the risk of sexually transmitted infections [9][10][11][12][13][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IPV is pervasive in Bangladesh and justified by more than one-third of the married women (Measure Demographic Health Surveys, 2012). Many married women feel that they cannot refuse to have sex with their husbands if their husbands have sexually transmitted infections (STIs; Jesmin & Cready, 2014). In a nationally representative sample of Bangladeshi married women, Decker et al (2008) found that 38% women experienced some form of violence in the 12 months preceding the survey.…”
Section: Cultural Contextmentioning
confidence: 99%
“…women and young adults). Thus appropriate programming for mass media can be very effective in informing people especially adolescents [12][13][14][15] . Moreover, among multiple accessible methods, using leaders of student groups as peer educator-mentor could have a mesmerizing influence on students' attitude [11] .…”
Section: Discussionmentioning
confidence: 99%